Transdisciplinary sustainability research in real-world labs: success factors and methods for change - Bergmann, Matthias; Schäpke, Niko; Marg, Oskar; Stelzer, Franziska; Lang, Daniel J.; Bossert, Michael; Gantert, Marius; Häußler, Elke; Marquardt, Editha; Piontek, Felix Maximilian; Potthast, Thomas; Rhodius, Regina; et al. (Sustainability science, 2021)
The transdisciplinary research mode has gained prominence in the research on and for sustainability transformations. Yet, solution-oriented research addressing complex sustainability problems has become complex itself, with new transdisciplinary research formats being developed and tested for this purpose. Application of new formats offers learning potentials from experience. To this end, we accompanied fourteen research projects conceptualized as real-world labs (RwLs) from 2015 to 2018. RwLs were part of a funding program on ‘Science for Sustainability’ in the German federal state of Baden-Württemberg. Here, we combine conceptual and empirical work to a structured collection of experiences and provide a comprehensive account of RwLs. First, we outline characteristics of RwLs as transformation oriented, transdisciplinary research approach, using experiments, enabling learning and having a long-term orientation. Second, we outline eleven success factors and concrete design notes we gained through a survey of the 14 RwLs: (1) find the right balance between scientific and societal aims, (2) address the practitioners needs and restrictions, (3) make use of the experimentation concept, (4) actively communicate, (5) develop a ‘collaboration culture’, (6) be attached to concrete sites, (7) create lasting impact and transferability, (8) plan for sufficient time and financial means, (9) adaptability, (10) research-based learning, and (11) recognize dependency on external actors. Characteristics and success factors are combined to illustrate practical challenges in RwLs. Third, we show which methods could be used to cope with challenges in RwLs. We conclude discussing the state of debate on RwLs and outline future avenues of research.